A note on Euler method for the overdamped generalized Langevin equation with fractional noise. (January 2021) - Dai, Xinjie; Xiao, Aiguo
Abstract: This paper generalizes the existing convergence result of Euler method for the overdamped generalized Langevin equation with fractional noise by Fang and Li (2020). In particular, several new techniques are developed.